2021
DOI: 10.3390/en14154449
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Evaluation of the Feasibility of Positive Energy Districts in Selected Urban Typologies in Vienna Using a Bottom-Up District Energy Modelling Approach

Abstract: This article investigates the potential of selected urban typologies in Vienna to reach the state of Positive Energy Districts (PED) by achieving a positive annual energy balance. It follows the EU initiative for implementing at least 100 PED in Europe by 2025. Four urban typologies have been assessed using the bottom-up energy modelling tool MAPED that enables a simplified energy demand-supply analysis at the district scale. Considering relevant urban typologies in different construction periods, the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A definition that is to be equally achievable in an urban context must therefore take this into account and refrain from a static target value. There are two aspects to consider here: First, this is simply a consequence of the physical facts, as detailed in [15,31,42]. However, there is a second point: in principle, the PED concept should not be opinionated about when and where it can be achievable and how easily.…”
Section: Ped Alpha Context:density and The Feasibility For Ped Distri...mentioning
confidence: 99%
See 1 more Smart Citation
“…A definition that is to be equally achievable in an urban context must therefore take this into account and refrain from a static target value. There are two aspects to consider here: First, this is simply a consequence of the physical facts, as detailed in [15,31,42]. However, there is a second point: in principle, the PED concept should not be opinionated about when and where it can be achievable and how easily.…”
Section: Ped Alpha Context:density and The Feasibility For Ped Distri...mentioning
confidence: 99%
“…A 2021 study on the PED potential of urban typologies in Vienna, Austria, found that only detached housing districts can achieve a positive annual energy balance (for heat and power) of 110%, whereas more dense typologies fail to achieve the criteria with an annual balance ranking between 61% and 97% [42].…”
Section: Figure 6 Illustration Of the Physical Difference Between Hig...mentioning
confidence: 99%
“…This Editorial article provides a summary of the Special Issue of Energies, covering the published papers [1][2][3][4][5][6][7][8] which address several of the topics mentioned in the Introduction. Table 1 identifies the most relevant topics in each published paper.…”
Section: Published Papers Highlightsmentioning
confidence: 99%
“…Analysis and Evaluation of the feasibility of Positive Energy Districts in selected urban typologies in Vienna is presented in article [4] by Hans-Martin Neumann et al, which investigates the potential of selected urban typologies in Vienna to reach the state of Positive Energy Districts (PED) by achieving a positive annual energy balance. Considering relevant urban typologies in different construction periods, the analysis focused on converting the allocated building stocks into PED by employing comprehensive thermal refurbishment and energy efficiency measures, electrification of end-uses and fuel switching, exploitation of local renewable energy potential, and flexible interaction with the regional energy system.…”
Section: Published Papers Highlightsmentioning
confidence: 99%
“…For this project, we considered 'innovation' as defined in different fields including 'technology and innovation', where innovation can be understood as connected to knowledge spillovers which can improve energy efficiencies [8], also economics and business, where innovation is sometimes an entrepreurial aim related to profit, and also as understood in the social sciences, urbanism and urban studies fields, connected with justice [9], behaviour change post-Covid [10], learnings for social innovation [11] and about measurement and feedback [12] from emerging Positive Energy Districts (PED). However, as one aspect of the +CityxChange project is behaviour change, and about new and future ways to live and create in the city, we concentrate on bottom-up citizen participation and urban change [13]. In general terms, we accept the definition of Katz (2014) that 'Innovation is when new or improved ideas, products, services, technologies, or processes create new market demand or cutting-edge solutions to economic, social and environmental challenges' [14].…”
Section: Innovationmentioning
confidence: 99%